Cholecystokinin is involved in triglyceride fatty acid uptake by rat adipose tissue. Issue 3 (March 2018) - Plaza, Adrián; Merino, Beatriz; Cano, Victoria; Domínguez, Gema; Pérez-Castells, Javier; Fernández-Alfonso, M Soledad; Sengenès, Coralie; Chowen, Julie A; Ruiz-Gayo, Mariano
Abstract : The incorporation of plasma triglyceride (TG) fatty acids to white adipose tissue (WAT) depends on lipoprotein lipase (LPL), which is regulated by angiopoietin-like protein-4 (ANGPTL-4), an unfolding molecular chaperone that converts active LPL dimers into inactive monomers. The production of ANGPTL-4 is promoted by fasting and repressed by feeding. We hypothesized that the postprandial hormone cholecystokinin (CCK) facilitates the storage of dietary TG fatty acids in WAT by regulating the activity of the LPL/ANGPTL-4 axis and that it does so by acting directly on CCK receptors in adipocytes. We report that administration of CCK-8 (a bioactive fragment of CCK) to rats: (i) reduces plasma ANGTPL-4 levels; (ii) represses Angptl-4 expression in WAT and (iii) simultaneously enhances LPL activity in this tissue without inducing Lpl expression. In vivo CCK-8 effects are specifically antagonized by the CCK-2 receptor (CCK-2R) antagonist, L-365, 260. Moreover, CCK-8 downregulates Angptl-4 expression in wild-type pre-adipocytes, an effect that is not observed in engineered pre-adipocytes lacking CCK-2R. These effects have functional consequences as CCK-8 was found to promote the uptake of dietary fatty acids by WAT, as demonstrated by means of proton nuclear magnetic resonance ( 1 H-NMR). The efficacy of acute CCK-8 administration was not reduced after chronic CCK-8 treatment. Moreover, the effects of CCK-8 on WAT were not associated to the increase of circulating insulin. Our results show that cholecystokinin promotes lipid storage in WAT by acting on adipocyte CCK-2R, suggesting a pivotal role for CCK in TG homeostasis.